Effects of Irrational Parenthood Cognition, Post Traumatic Stress Disorder and Spousal Support on Quality of Life of Infertile Women - So Ra Yang; Jung Hee Yeo (Korean Society of Women Health Nursing, 2017)
PURPOSE: This study examined degrees of irrational parenthood cognition, post traumatic stress disorder (PTSD), spousal support, and quality of life and investigated factors that influence the quality of life of infertile women. METHODS: Research design was a cross sectional correlational survey with a total of 113 female patients receiving treatment for infertility. Data were collected from August 1 to November 30, 2015. The collected data were analyzed using t-test, ANOVA, Pearson's correlation, and multiple regression analysis. RESULTS: The mean score of the quality of life was 59.0±14.8. The quality of life was significantly associated with irrational parenthood cognition (r=-.70), post traumatic stress disorder (r=-.65), and spousal support (r=.56). The factors significantly affecting the quality of life in infertile women were irrational parenthood cognition (β=-.45), post traumatic stress disorder (β=-.34), and spousal support (β=.32). The explained variance by these factors was 70.4%, and the regression model was valid (F=89.81, p<.001). CONCLUSION: This study may contribute to the development of nursing intervention program to improve the quality of life of infertile women.